Adverse effects from antidepressant treatment: Randomised controlled trial of 601 depressed individuals - Crawford, A; Lewis, S; Nutt, D; Peters, T; Cowen, P; O'Donovan, M; Wiles, N; Lewis, G (Springer Berlin Heidelberg, 2014)
Rationale: Premature discontinuation of antidepressant drugs is a frequent clinical problem. Adverse effects are common, occur early on in treatment and are reported to be one of the main reasons for discontinuation of antidepressant treatment. Objectives: To investigate the association between adverse effects occurring in the first 2 weeks of antidepressant treatment and discontinuation by 6 weeks as the outcome. To investigate the time profile of adverse effects induced by the selective serotonin reuptake inhibitor citalopram and the noradrenaline reuptake inhibitor reboxetine over 12 weeks of treatment. Methods: Six hundred and one depressed individuals were randomly allocated to either citalopram (20 mg daily) or reboxetine (4 mg twice daily). A modified version of the Toronto Side Effects Scale was used to measure 14 physical symptoms at baseline (medication free) and at 2, 6 and 12 weeks after randomisation. Results: Individuals randomised to reboxetine reported a greater number of adverse effects and were more likely to stop treatment than individuals receiving citalopram. Dizziness (OR 1.83; 95% CI 1.09, 3.09; p = 0.02) and the total number of adverse effects (OR 1.12; 95% CI 1.00, 1.25; p = 0.06) reported at 2 weeks were associated with discontinuation from overall antidepressant treatment by 6 weeks. Reports of adverse effects tended to reduce throughout the 12 weeks for both antidepressants. Conclusions: The majority of adverse effects were not individually associated with discontinuation from antidepressant treatment. Reports of physical symptoms tended to reduce over time. The physical symptoms that did not reduce over time may represent symptoms of depression rather than antidepressant-induced adverse effects. © 2014 The Author(s).